2011
DOI: 10.1001/archpediatrics.2010.247
|View full text |Cite
|
Sign up to set email alerts
|

Community Treatment of Posttraumatic Stress Disorder for Children Exposed to Intimate Partner Violence

Abstract: To evaluate community-provided traumafocused cognitive behavior therapy (TF-CBT) compared with usual community treatment for children with intimate partner violence (IPV)-related posttraumatic stress disorder (PTSD) symptoms. Design: Randomized controlled trial conducted using blinded evaluators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
251
3
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(267 citation statements)
references
References 20 publications
9
251
3
4
Order By: Relevance
“…Our rate of attrition was comparable to clinic-based trauma intervention research (Cohen et al, 2011), but higher than other school-based studies, which have shown attrition rates as low as 9% (Jaycox et al, 2010). While we did not find systematic demographic differences between treatment completers and those who attrited from the treatment groups, future research is needed on the reasons for which youth may drop out of school-based treatment, which is typically much more accessible than clinic-based care (Jaycox et al, 2010).…”
Section: Study Strengths and Limitationssupporting
confidence: 59%
See 1 more Smart Citation
“…Our rate of attrition was comparable to clinic-based trauma intervention research (Cohen et al, 2011), but higher than other school-based studies, which have shown attrition rates as low as 9% (Jaycox et al, 2010). While we did not find systematic demographic differences between treatment completers and those who attrited from the treatment groups, future research is needed on the reasons for which youth may drop out of school-based treatment, which is typically much more accessible than clinic-based care (Jaycox et al, 2010).…”
Section: Study Strengths and Limitationssupporting
confidence: 59%
“…The 25% attrition rate of youth who began treatment is comparable to that of trauma treatment studies with similar populations in clinical outpatient contexts (e.g., Cohen, Mannarino, & Iyengar, 2011). However, other youth trauma interventions have shown decreased rates of attrition as well as increased initial intervention uptake (i.e., rate of initiating treatment after randomization).…”
Section: Methods Participantsmentioning
confidence: 66%
“…Anneannenin ise, torununu 'yıllar önce kaybettiği kızının' yerine koyarak, 'onu yanından hiç ayırmayarak', kendi kızı ile kuramadığı, özlediği ilişkiyi torunu ile kurabildiği söylenebilir. Çalışmamızda belirtilen olgu örneğinde olduğu gibi, çoğul ve uzun süreli travma deneyimi olan kadınlar TSSB açısından risk taşırlar; sağaltımları konusunda uygun yöntemlerin seçilmesi, koruyucu ruh sağlığı uygulamaları açısından önemlidir (11,12). Bu nedenle, farklı yaşam biçimleri ile bölgelere özgü sosyoekonomik -kültürel değişkenlerin iyi tanınması ve bu değişkenlerin ruhsal belirtiler ile iliş-kisinin sorgulanmasının ulusal sağlık programlarımıza ışık tutacağı inancındayız.…”
Section: Discussionunclassified
“…A comprehensive review of all evidence-based modalities is beyond the scope of this review. However, two examples of effective interventions, Trauma Focused Cognitive Behavior Therapy 47) and Child and Family Traumatic Stress Intervention 48) will highlight components and strengths common to many interventions. Additional information, including information on interventions can be found on the National Child Traumatic Stress Network website (http://nctsn.…”
Section: Psychotherapeutic Interventionsmentioning
confidence: 99%
“…47) Children and adolescents who benefit from TF-CBT include those with PTSD, anxiety, depressive or externalizing behaviors. Randomized controlled trials comparing TF-CBT efficacy against other psychotherapies have been performed by multiple investigators who have replicated findings of the original treatment developers.…”
Section: Trauma Focused Cognitive Behavioral Therapymentioning
confidence: 99%